Features of secondary prevention in young STEMI patients. (14th October 2021) - Bilyi, D; Parkhomenko, A N; Irkin, O I; Lutai, Y M; Stepura, A O; Dovhan, O V
Abstract:  : Among patients who underwent a myocardial infarction (MI), one in five patients has a second cardiovascular event (MI, acute cerebrovascular accident, arrhythmias, etc.) during the first year, even with optimal treatment and care. Young patients often do not take the prescribed treatment or do not take it for a long time after discharge from the hospital. The issue of secondary prevention among the population is well studied, while in the literature such data for young people are lacking. Methods: The data of 160 STEMI young patients (18–46 years) who admitted and treated in the intensive care unit were evaluated. We studied the effect of the main groups of medicines on the course of AMI in young patients. The remote observation lasted 5 years after discharge from the hospital. The following cardiovascular events during 1 (365 days), 2 (730 days), 3 (1095 days), and 5 years (1800 days) of the FU were used as the endpoint: death from any cause, combined endpoint (cardiovascular death, myocardial infarction, stroke, revascularization (CABG, stenting). Results: It was noted that taking one of the antithrombotic drugs (clopidogrel or ticagrelor) in young patients, after 2, 3, and 5 years of follow-up, significantly affected the development of the combined endpoint, reducing the number of events (p=0.013, p=0.004 and p=0.048, respectively). Statins had a better effect on the number of combined endpoints (reduced their number) in young patients during 2-year and 3-year follow-up (p=0.041) and (p=0.034), respectively. In young patients, ACEI or ARB tended to influence the development of a combined endpoint at 2, 3, and 5 years of follow-up (p=0.061, p=0.080, and p=0.067, respectively). In our study, we found that taking aspirin at a dose of 75–100 mg tends to reduce the development of death from any cause (p=0.054) within 5 years (1800 days) from discharge. Patients under 45 years after undergoing AMI were significantly less likely to take the minimum necessary medication, like aspirin, and statins than older patients (45–65 years) (24.2% vs. 42%, p<0.001, respectively). Conclusion: Young patients after AMI for secondary prevention must take an antithrombotic drug (clopidogrel or ticagrelor), statins, and an ACEI or ARB. In order to increase compliance, it is recommended to take a combination drug. FUNDunding Acknowledgement: Type of funding sources: None.